Dissertation for the design and fabrication of motorized food packer / Muhammad Haziq Irfan Yusrizam - Yusrizam, Muhammad Haziq Irfan (2023)
Most of Malaysian vendors prefer to use food plastics to pack up their customers foods as it is cheap and plentiful to buy everywhere. But as it requires tying unlike plastic and polystyrene food packs, it is very time consuming and troublesome. Not to forget, calculating customers’ total purchases also contributes to this problems , which the main objective of this project is to eliminate these problems. A food plastic tying string is pulled out from a ready-made slot in the machine. The user only has to load the food packaging to the machine and pull the plastic to tie the food quickly without spending a lot of time tying using the traditional way. The machine itself rely on the tying mechanism triggered by two components: weight and sensor. It is expected for this machine to tie (pack) the food when it exceeds set weight limit.